PENGARUH CAPITAL EMPLOYED, HUMAN CAPITAL, STRUCTURAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA - GRACE LORDITA HATUMENA; TITIEK RACHMAWATI; NEKKY RAHMIYATI (GANEC SWARA, 2024)
This study aims to analyze the effect of capital employed, human capital, structural capital on financial performance in manufacturing companies in the basic and chemical industry sector including the cement sub-sector and the ceramics, porcelain and glass sub-sector listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The sampling technique used in this study uses data collection techniques with certain considerations (purposive sampling), namely manufacturing companies in the basic and chemical industry sectors including the cement sub-sector and the ceramics, porcelain and glass sub-sectors listed on the Indonesia Stock Exchange (IDX) during 2020-2022. The data analysis method used is multiple linear regression analysis method. The hypothesis tests used are t test, F test and coefficient of determination. The results showed that Capital Employed and Structural Capital had no effect on Financial Performance. This proves that if the capital and structure used by the company changes, financial performance will not change or remain. While Human Capital has an effect on Financial Performance. This is because the company has the ability to utilize the quality of its human resources, the lack of salaries and benefits provided by the company to employees.